Respiratory symptoms and duration of residence in immigrant teenagers living in Melbourne, Australia. Issue 2 (1st August 1999) - Powell, C V E; Nolan, T M; Carlin, J B; Bennett, C M; Johnson, P D R
Abstract : OBJECTIVE: Examination of the relation between respiratory symptoms and time since arrival in Australia in immigrant teenagers living in Melbourne. DESIGN: Two stage, stratified, cross sectional survey. SETTING: High schools (n = 51). SUBJECTS: 9794 people aged 13–19 years. MAIN OUTCOME MEASURES: Prevalence of wheeze during a 12 month period, region of birth, duration of residence in Australia. RESULTS: The estimated population 12 month period prevalence of wheeze was 18.9% (95% confidence interval (CI), 18.0 to 19.9). In subjects born outside Australia, residence for five to nine years in Australia was associated with a 2.1-fold (CI, 1.1 to 4.0) increase in the odds of self reported wheeze; after 10–14 years, this risk increased 3.4-fold (CI, 1.8 to 6.7). There was no difference in severity of wheeze, measured by reported frequency of attacks, between Australian born and non-Australian born subjects. CONCLUSIONS: The notion of a continued secular increase in the prevalence of wheezing is not supported. There is a time dose effect on the prevalence of symptoms in subjects born outside Australia and now living in Melbourne, which is independent of age and country of birth.